Effects of Endoparasitism of Heteropneustes fossilis on condition factor, gonad and blood composition of host - Khalil, Sarker M Ibrahim; Chandra, Kirtunia Juran; Das, David Rintu (Research in Agriculture Livestock and Fisheries, 2015)
Effects of endoparasitism of Heteropneustes fossilis on condition factor, gonad and blood composition of the host was conducted during July 2012 to June 2013. Fish samples were collected from various water bodies of Sylhet region. Total length, body weight, gonad weight and sex of hosts were recorded. Blood sample was collected from each fish. Six different species of parasites were identified from the hosts assessed as i). Euclinostomum multicaecum, ii) Allocreadium handiai, iii). Lytocestus indicus, iv). Pseudocaryophyllaeus heteropneustus, v). Procamallanus heteropneustus and vi). Paracamallanus equispiculus. Gonad weight, condition factors and blood parameters of H. fossilis were greatly affected with moderate infestations. The highest condition factor, 0.59, was found in uninfested fish and lowest, 0.45, in infested fish. Changes in the percent of haemoglobin and erythrocyte sedimentation rate (ESR) was also investigated. Percent loss of haemoglobin was 0.43 and erythrocyte sedimentation rate (ESR) was 5.19 mm/h. In general the health condition parameter due to effects of endoparasitism of the investigated fish was found negative impact for the culture production of the Singhi (Heteropneustes fossilis). DOI: http://dx.doi.org/10.3329/ralf.v1i1.22379 Res. Agric., Livest. Fish.1(1): 159-167, Dec 2014